Análise in vitro da resistência à tração e à fadiga, em função do tempo de uso, dos componentes de retenção de sobredentaduras sobre implantes - Santos, Paulo Henrique dos (2011)
This study evaluated and compared the resistance to pulling forces of the three components of retention of overdentures in the initial stage and after a simulated test of fatigue during the period of 6, 12, 24, 36 and 60 months. Systems constituted three groups: G1-Bar-Clip, G2- ERA and G3- O-Ring. Three specimens made of colorless resin were used. In the body of evidence from G1 were inserted two implants, which was screwed a bar with two uclas. In G2 and G3 was an implant inserted in each block and installed them on their retention abutments. Each base has a handle, stainless steel wire at the top to allow its use in the universal testing machine mechanical K500 SMP-KRATOS and wear machine thermomechanical 37000 ER - training staff to fatigue. At each measurement period and each component was changed to retain each group, with a total of 75 components, 25 per group. The results showed the average amount of holding force of each system and the changes after simulated test of fatigue. The Bar-Clip system and the ERA had values in the force of traction statistically similar and superior to the system O-Ring. This in turn showed a higher wear within 6 months, had the smallest change in subsequent periods. The research helped to clarify the average values of the holding force of each studied system and its behavior as a function of time of use, which guides professionals in choosing these systems according to the clinical situation presented